Resilience of The Cempaka Cilangkap Cipayung Park Tourism Object Through The Completeness and Quality of Tourism Facilities - Latif, Bagus Syarifuddin; Nugraha, Rizki Nurul (West Science Business and Management, 2024)
This research is entitled "Resilience of the Cempaka Cilangkap Cipayung Park Tourist Object through the Completeness and Quality of Tourist Facilities." The choice of this title was based on the interest in exploring the resilience of the Taman Cempaka tourist attraction, with a special focus on the extent to which the completeness and quality of tourist facilities influence the resilience of the Taman Cempaka Cilangkap Cipayung tourist attraction with the research location located on Jl. Setu Cipayung, Taman Cempaka, Cipayung District, East Jakarta City. The method used is a qualitative descriptive method, with the research objective being to find out how influential the quality and availability of facilities at Taman Cempaka Cilangkap are on visitor satisfaction and the level of sustainability of Taman Cempaka which is expected to provide a basis for improving facilities, more effective destination management, as well as formulating appropriate policies. supports the sustainability of Cempaka Cilangkap Cipayung Park as a strong tourist attractio